3D in vitro blood–brain barrier models: recent advances and their role in brain disease research and therapy - O’Halloran, Laura; Akinsete, Olutoyosi; Kogan, A. Leah; Wrona, Michelle; Mahdi, Amira F. (Frontiers in Pharmacology, 2025)
The blood-brain barrier (BBB) is a dynamic and highly selective interface crucial to central nervous system (CNS) homeostasis, presenting a major challenge for effective drug delivery in treating CNS pathologies such as brain tumours and neurodegenerative disease. Traditional two-dimensional (2D) in vitro models and animal models often fail to replicate the structural complexity and physiological functions of the human BBB. Recent advances in three-dimensional (3D) in vitro modelling offer enhanced physiological relevance by integrating cellular architecture, extracellular matrix (ECM) components, and dynamic fluid flow to simulate in vivo conditions more accurately. This review explores the structural and functional features of the BBB and highlights the evolution from 2D to 3D in vitro models, including hydrogel-based systems, microfluidics, organ-on-a-chip (OOAC) platforms, spheroids and organoids. The advantages of these models in recapitulating BBB dynamics and their application in cancer research and other CNS diseases are discussed. Finally critical comparison and discussion of current 3D models is presented, highlighting differences and best potential uses of each variation. Continued advancements are needed to develop accurate 3D in vitro models of the BBB in order to revolutionize drug screening, predict therapeutic efficacy, and support personalized medicine approaches. By providing robust, human-relevant platforms, 3D BBB models can accelerate drug development and treatment for patients affected by CNS pathologies.